A Cross Sectional Study on Visual Health among Women aged 18-59 years residing in a Slum of Kolkata, West Bengal - Sembiah, Sembagamuthu; Paul, Bobby; Dasgupta, Aparajita; Biswas, Bijit; Ghosh, Ayon; M, Manjula (Indian Journal of Community Health, 2017)
Introduction: Visual impairment has a silent chronic course which has a significant impact on the quality of life but is often a preventable community problem. Comprehensive assessment of ophthalmic outcomes should include not only the objective measurement but also the subjective perception of vision loss on vision function. Aim: To estimate the proportion of visual impairment and perceived visual functioning and also to find out the factors, if any associated with it, among women aged18-59 years in a slum of Kolkata. Methodology: It was a community-based cross-sectional study conducted among 153 women aged 18-59 years residing in a slum of Chetla, which is under the urban field practice area of All India Institute of Hygiene & Public Health, Kolkata within 3 months of duration (Mar - May 2017). Results: In the present study, 49(32%) study subjects were visually impaired among which 3(2%) were blind. 42.4% of study subjects’ perceived poor visual function. Logistic regression showed aged 40 years and above, below and primary educational level, non-working, who had eye checkup and diabetic had higher odds of visual impairment and perceived poor visual function whereas after adjustment, diabetic status lost its significance. Conclusion: Eye care programmes in our country still have curative approach; it must shift towards preventive approach.